2008
DOI: 10.2114/jpa2.27.295
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Daily Walking Steps with Calcaneal Ultrasound Parameters and a Bone Resorption Marker in Elderly Japanese Women

Abstract: Quantitative ultrasound (QUS) parameters of the calcaneus and bone resorption markers predict osteoporotic fractures. High levels of physical activity have positive effects on bone health. The purpose of this cross-sectional study was to investigate the effects of daily walking activity (number of steps taken), as an outcome of physical activity, on QUS parameters of the calcaneus and urinary deoxypyridinoline (DPD) in elderly Japanese women. The subjects were 113 postmenopausal women aged 60-85 years. The spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 44 publications
2
18
0
2
Order By: Relevance
“…With respect to walking ability, Kwon et al reported that a decline in gait speed was associated with decreased BMD in a longitudinal observation of c o m m u n i t y -d w e l l i n g e l d e r l y w o m e n 9 ) . Furthermore, Ki tagawa et al reported a relationship between the number of daily walking steps and QUS 16,17) . The results of these previous studies demonstrate that walking ability is related to BMD and QUS, but the relationship between BMD or QUS and TUGT was not investigated in these previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to walking ability, Kwon et al reported that a decline in gait speed was associated with decreased BMD in a longitudinal observation of c o m m u n i t y -d w e l l i n g e l d e r l y w o m e n 9 ) . Furthermore, Ki tagawa et al reported a relationship between the number of daily walking steps and QUS 16,17) . The results of these previous studies demonstrate that walking ability is related to BMD and QUS, but the relationship between BMD or QUS and TUGT was not investigated in these previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…Our observations confirm results from other researches. [21][22][23] This can indicate that heel ultrasound is more useful in detecting activity-related bone remodelling than DXA. More notice should also be paid to this body site as the first line of changes in regular activity.…”
Section: Quantitative Ultrasound and Activity-related Bone Statusmentioning
confidence: 99%
“…E, marcadores de reabsorção óssea em níveis elevados têm sido relacionados a altos riscos de fraturas osteoporóticas. Assim, manutenção da densidade mineral óssea (DMO) adequada e baixos níveis desses biomarcadores podem ser considerados fatores de prevenção de fraturas osteoporóticas 4 . A DXA, ainda pouco acessível e de custo elevado, detecta o remodelamento num período mínimo de três a seis meses.…”
Section: Descriptores: Densidad óSea Metabolismo Ejercicio Mujeresunclassified
“…Dore et al 11 constataram correlação dos passos diários com a DMO, medida pela DXA, em 740 sujeitos, média de 62 anos, sendo 52% mulheres na pós-menopausa. Kitagawa et al 4 demonstraram associação positiva dos passos diários com a DMO medida pelo ultrassom (US) de calcâneo.…”
Section: Descriptores: Densidad óSea Metabolismo Ejercicio Mujeresunclassified